EKSISTENSI HUKUM ADAT PERKAWINAN MASYARAKAT BAYAN DI KABUPATEN LOMBOK UTARA - Oktaria Ningsih (Fakultas Hukum Universitas Gunung Rinjani, 2019)
The Bayan villagers are known as the Bayan Indigenous Peoples, where in their lives, they always apply customary law rules without abandoning state and religious law, one of which is related to marriage. This study aims to determine and analyze the existence of customary law in the aspects of the social and cultural life of the Bayan Village community and what factors are supporting and inhibiting the existence of customary law in the socio-cultural aspect of the Bayan Village community. The approach used is a qualitative approach with an empirical sociology method. The sampling technique is the Purposive Sampling technique. Sources of data in this study are primary and secondary data sources. To collect research data observation, interview, documentation and literature study techniques are used. Furthermore, the data that has been obtained from the field are analyzed by comparison, then analyzed to draw generalizations or conclusions. This research concludes that up to now the Bayan community has always carried out traditional marriages with a marriage system called Mulang, which in the process began with the Mulang implementation, which at the peak of the event was carried out by the Customary Marriage tradition. This proves that until now the existence of customary law in the socio-cultural life of the community is still strong. The factors that support the existence of customary law in life are: 1) The concept of life of the Bayan community, 2) The existence of Bayan adat institutions in overseeing Bayan customary law, and 3) The strict sanctions of customary law that apply to Bayan villagers. Furthermore, in general fatktor that impedes it is the desire of local people to change their living systems and the lack of Bayan young people who respect the value of customs.